Melatonin alleviates ovariectomy-induced cardiovascular inflammation in sedentary or exercised rats by upregulating SIRT1 - ERCAN, FERİHA; YILDIRIM, ALPER; YEGEN, BERRAK (My University, 2022)
© 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.We aimed to evaluate the impact of hormone replacement, melatonin, or exercise alone or their combination on oxidative damage and functional status of heart, brain, and aorta of ovariectomized (OVX) rats and to determine whether the signaling pathway is dependent on sirtuin-1 (SIRT1). Ovariectomized Sprague Dawley rats were orally given either a hormone replacement therapy (1 mg/kg/day,17β estradiol; HRT) or melatonin (4 mg/kg/day) or HRT + melatonin treatments or tap water, while each group was further divided into sedentary and exercise (30 min/5 days/week) groups. After the heart rate measurements and memory tests were performed, trunk blood was collected at the end of the 10th week to determine metabolic parameters in serum samples. Tissue samples of abdominal aorta, heart, and brain were taken for biochemical measurements and histopathological evaluation. Heart rates and memory performances of the OVX rats were not changed significantly by none of the applications. Melatonin treatment or its co-administration with HRT upregulated the expressions of IL-10 and SIRT1, reduced the expressions of IL-6 and TNF-α, and reduced DNA damage in the hearts and thoracic aortae of non-exercised rats. Co-administration of melatonin and HRT to exercised OVX rats reduced inflammatory response and upregulated SIRT1 expression in the aortic and cardiac tissues. The present study suggests that melatonin treatment, either alone or in combination with exercise and/or HRT, upregulates SIRT1 expression and alleviates oxidative injury and inflammation in the hearts and aortas of OVX rats. Melatonin should be considered in alleviating cardiovascular disease risk in postmenopausal women.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Fizyoloji; Medicine; Health Sciences; Fundamental Medical Sciences; Human Physiology; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Biyoloji ve Biyokimya; TIP, GENEL & DAHİLİ; FİZYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; BIOLOGY & BIOCHEMISTRY; MEDICINE, GENERAL & INTERNAL; PHYSIOLOGY; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Fizyoloji (tıbbi); Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Yaşam Bilimleri; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Physiology (medical); Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Physiology; Life Sciences; melatonin; hormone replacement therapy; exercise; cardiovascular disease; sirtuin-1; HORMONE REPLACEMENT THERAPY; DENSITY-LIPOPROTEIN CHOLESTEROL; CORONARY-HEART-DISEASE; RISK-FACTORS; OXIDATIVE STRESS; ISCHEMIA/REPERFUSION INJURY; MYOCARDIAL-INFARCTION; POSTMENOPAUSAL WOMEN; ESTROGEN; MENOPAUSE; melatonin; hormone replacement therapy; exercise; cardiovascular disease; sirtuin-1